The role of ROS1 mutation in non-small cell lung cancer - Novita Andayani; Basti Handoko; Murtaza (Surgical Residency Program Syiah Kuala University, 2022)
Lung cancer is a malignancy of the lung organs consisting of primary lung cancer originating from lung epithelial cells and metastatic lung cancer originating from other organ cancers that spread. In lung cancer, the vast of recent studies investigated the role of molecular alterations in patients. Molecular characterizations of lung cancer give further information in order to better diagnosis, prognostic, and therapeutic implications in patients. c-ROS oncogene 1 (ROS 1) is naturally expressed by healthy and normal cells arranged in human chromosomes. The role of ROS1 in its normal development is not fully understood. Point of view in oncology ROS1 expressed normally is referred to as inactive ROS1. Mutated ROS1 due to fusion with a specific gene produces tyrosine kinase receptors on the surface of the cell that has the advantage of sending signals into the cells to induce growth factors and proliferation of ROS1. Although the prevalence of ROS1 rearrangement was low, the parallel with Non-Small Cell of Lung Cancer (NSCLC), the most dominant lung cancer, indicating the number of ROS1 mutation patients also increased. The challenge of diagnosing ROS1 mutation by Immunohistochemical (IHC) ROS1 is only a screening method and confirmed by fluorescence in situ hybridization (FISH) examination. The appropriate therapy regimen for positive ROS1 mutation will increase the survival rate in lung cancer patients.